A robust-based fatigue optimization method for systems subject to uncertainty - Rosa, U. L.; de Lima, A. M. G.; Gonçalves, L. K. S.; Belonsi, M. H. (Journal of mechanical science and technology, 2022)
A robust design method based on fatigue for stochastic problems is proposed. In most cases, fatigue analyses of structures are performed by assuming the nominal values of their parameters in a deterministic way. However, since the systems are frequently subject to parametric uncertainty and random forces simultaneously, it does not provide a representative fatigue index. Thus, it becomes essential to consider these uncertainties on the fatigue models. Here, a plate stochastic finite element is used to formulate the probabilistic Sines’ index in frequency-domain, where the random fields are discretized using Karhunen-Loève expansion with hypercube sampling as stochastic solver. To maximize fatigue performance, a robust optimization combined with a robust reduction is proposed to increase the efficiency of the method. The envelopes of stresses and the Sines’ coefficients for optimized solutions confirm the importance of considering uncertainty on fatigue models for more realistic situations.